Linguistic–Cultural Mediation in Asylum and Refugee Settings and Its Emotional Impact on Arabic–Spanish Interpreters - Bachir Mahyub-Rayaa; Moulay-Lahssan Baya-Essayahi (European Journal of Investigation in Health, Psychology and Education, 2021)
Emotional factors in linguistic–cultural mediation have attracted the attention of prior literature for a number of decades, both regarding the cognitive processes involved in language interpreting and the impact of stress and emotion on the performance of interpreters. However, research has not yet been replicated in the Arabic–Spanish pair, despite it being one of the combinations most requested by public services in Spain and Europe. Methodology: An exploratory study conducted by an anonymous online 17-item survey was carried out in order to discover the perception of Arabic–Spanish interpreters in asylum and refugee settings about the emotional impact of their job. Out of 30 contacted, 23 active interpreters completed the survey. Results: The answers showed that all of the interpreters had been exposed to situations that had emotionally impacted them. Triggering situations and a list of negative emotions were collected. Discussion: Direct and indirect implications of the referred emotional episodes and their consequences on the performance of the interpreters were analysed and discussed. Conclusions: Linguistic–cultural mediation in these settings exposes interpreters to harsh stories that trigger mostly negative emotions. These professionals lack psychological support; thus, they are forced to deal individually with each situation, without taking into account the possible consequences on their work and their physical and mental health.